4. CLINICAL AND PARACLINICAL CHARACTERISTIC OF BLUNT SPLENIC PATIENTS UNDERGOING SPLENECTOMY AT MILITARY HOSPITAL 103 (Vietnam Journal of Community Medicine, 2023)
Objective: Splenic rupture is a common injury in blunt abdominal trauma, often in the setting of multiple trauma. Clinical and paraclinical evaluation is very important to have the attitude and to choose the treatment method urgently and appropriately for the patient. Aim: Study clinical and paraclinical characteristics of patients undergoing splenectomy due to trauma. Subjects and methods: A prospective and cross-sectional study on 65 of blunt splenic patients undergoing Splenectomy at Military Hospital 103 from January 2019 to June 2023. Results: 58 patients with traumatic splenic rupture undergoing Splenectomy, the mean age was: 30.6±13.049 years old, the youngest was 7 years old, and the oldest was 67 years old. Patients of working age were 87.9%, male ratio was 77.6%, and traffic accidents were 70.7%. There was 32.8% of isolated blunt splenic injury, 48.3% of the patients admitted to the hospital in shock, the rate of not receiving first aid before the hospital was 53.4%, and the average time to hospital was 4.2. ± 4.402 hours. 100% of the patients received an emergency ultrasound in bed, the rate of abdominal computed tomography with contrast injection was 58.6%, the splenic injury grade on CT was not related to shock with p > 0.05. Conclusion: Spleen ruptured abdominal trauma was common in working age. The common cause was traffic accidents, mostly multiple traumas, patients did not receive first aid before the hospital, and the shock rate was high.
Keywords: Blunt splenic injury, abdominal trauma, splenectomy.